Pengaruh Kompetensi Sumber Daya Manusia Dan Kemampuan Pemanfaatan Teknologi Terhadap Kinerja Aparatur Desa Di Kantor Desa Jojjolo - Muhammad Bakri; Jainuddin Jainuddin; Risman Risman; Muhammad Erfan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Based on the review of the main problem, the research objectives to be achieved are as follows: (1) To determine and analyze the influence of Human Resource Competence on the Performance of Village Apparatuses at the Village Office in Jojjolo (2) To determine and analyze the influence of Technology Utilization Capability on Village Apparatus Performance At the Village Office In Jojjolo To find out, (3) To analyze the influence of Human Resource Competence and Ability to Utilize Technology on the Performance of Village Apparatus at the Village Office in Jojjolo. The research location is Jo'jolo Village, Bulukumpa District, Bulukumba Regency. This study uses descriptive qualitative research methods, with data sources, namely questionnaires and documentation. The sample of this research is village apparatus. The data analysis used is data quality test, classical/prerequisite test, and hypothesis testing. The potential of HR affects the performance of village officials. This means that the better the competence of human resources, the performance of the village apparatus will also increase. The use of technology has a significant influence on the performance of the village apparatus. This means that the better the use of technology, the performance of the village apparatus will increase. Keywords: Human Resources, Village Apparatus, Technology